Csn5 Is Required for the Conidiogenesis and Pathogenesis of the Alternaria alternata Tangerine Pathotype - Wang, Mingshuang; Yang, Xiao; Ruan, Ruoxin; Fu, Huilan; Li, Hongye (Frontiers in Microbiology, 2018)
The COP9 signalosome (CSN) is a highly conserved protein complex involved in the ubiquitin-proteasome system. Its metalloisopeptidase activity resides in subunit 5 (CSN5). Functions of csn5 in phytopathogenic fungi are poorly understood. Here, we knocked out the csn5 ortholog (Aacsn5) in the tangerine pathotype of Alternaria alternata. The ΔAacsn5 mutant showed a moderately reduced growth rate compared to the wildtype strain and was unable to produce conidia. The growth of ΔAacsn5 mutant was not affected in response to oxidative and osmotic stresses. Virulence assays revealed that ΔAacsn5 induced no or significantly reduced necrotic lesions on detached citrus leaves. The defects in hyphal growth, conidial sporulation, and pathogenicity of ΔAacsn5 were restored by genetic complementation of the mutant with wildtype Aacsn5. To explore the molecular mechanisms of conidiation and pathogenesis underlying Aacsn5 regulation, we systematically examined the transcriptomes of both ΔAacsn5 and the wildtype. Generally, 881 genes were overexpressed and 777 were underexpressed in the ΔAacsn5 mutant during conidiation while 694 overexpressed and 993 underexpressed during infection. During asexual development, genes related to the transport processes and nitrogen metabolism were significantly downregulated; the expression of csn1-4 and csn7 in ΔAacsn5 was significantly elevated; secondary metabolism gene clusters were broadly affected, especially, the transcript level of the whole of cluster 28 and 30 were strongly induced. During infection, the expression of the host-specific ACT toxin gene cluster which controls the biosynthesis of the citrus specific toxin was significantly repressed; many other SM clusters with unknown products were also regulated; 86 out of 373 carbohydrate-active enzymes responsible for breaking down the plant dead tissues showed uniquely decreased expression. Taken together, our results expand our understanding of the roles of csn5 on conidiation and pathogenicity in plant pathogenic fungi and provide a foundation for future investigations.